Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1016/j.rmed.2008.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index, respiratory function and bronchial hyperreactivity in allergic rhinitis and asthma

Abstract: This study provides the first evidence of a significant relationship between BMI and allergic rhinitis and between BMI and BHR in both allergic disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 31 publications
3
35
0
2
Order By: Relevance
“…Only one study by Ciprandi et al 9 reported a significant association between increased BMI and AR in males. This finding is conflicting with previous studies and with our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one study by Ciprandi et al 9 reported a significant association between increased BMI and AR in males. This finding is conflicting with previous studies and with our study.…”
Section: Discussionmentioning
confidence: 99%
“…studies have reported positive associations between increased BMI and AR. [9][10][11] Nevertheless, the mechanism for the association between respiratory allergic diseases and obesity and the reasons for the apparent difference between men and women remain unclear. 2 Because both respiratory allergic diseases and obesity are characterized by inflammation, a common inflammatory pathway has been proposed as a plausible explanation for the association between respiratory allergy and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…La influencia del IMC sobre las variables funcionales pulmonares de nuestros pacientes es más difícil de explicar. Un estudio reciente 23 provee la evidencia de una significativa correlación entre el IMC y la rinitis alérgica e hiperreactividad bronquial, pero ningún impacto en los parámetros funcionales demostrados en la espirometría. Aunque las evidencias no son unánimes, 24,25 los índices de masa corporal indicadores de obesidad pueden afectar la función respiratoria, con reducción del volumen y la capacidad pulmonar en ausencia de enfermedad respiratoria, y pueden exagerar ese efecto en una enfermedad de la vía aérea preexistente.…”
Section: Discussionunclassified
“…As age is not considered in school the presence or absence of AR in girls and boys regarding BMI distribution (Table 1). There are three studies in the literature which investigates the effect of high BMI values studies carried out by Ciprandi et al [18] and by us are based on clinical data and specialist diagnoses and posses a stronger base.…”
Section: Discussionmentioning
confidence: 99%
“…In another study carried out by Kilpeläinen et al [1] it was reported that high BMI values in women was the reason of increase in AR risk and did not effect males at all. In a study carried out by Ciprandi et al [18] a global relationship was determined between BMI values and AR and asthma.…”
Section: Discussionmentioning
confidence: 99%